2011
DOI: 10.1038/leu.2011.298
|View full text |Cite
|
Sign up to set email alerts
|

Differential prognostic effect of IDH1 versus IDH2 mutations in myelodysplastic syndromes: a Mayo Clinic Study of 277 patients

Abstract: Unlike the case with acute myeloid leukemia, there is limited information on the prognostic impact of isocitrate dehydrogenase (IDH) mutations in myelodysplastic syndromes (MDS). In the current study of 277 patients with MDS, IDH mutations were detected in 34 (12%) cases: 26 IDH2 (all R140Q) and 8 IDH1 (6 R132S and 2 R132C). Mutational frequency was 4% (2 of 56) in refractory anemia with ring sideroblasts, 12% (16 of 130) in refractory cytopenia with multilineage dysplasia, 14% (2 of 14) in MDS-unclassifiable,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(114 citation statements)
references
References 31 publications
2
110
1
1
Order By: Relevance
“…IDH2 mutant proteins promote AML by blocking the differentiation of HSPCs; in the absence of a cooperating event, this produces an MDS-like state, a disorder in which IDH2 mutations are frequent in humans (Patnaik et al 2012). While these effects correlate with the ability of IDH2 mutants to produce 2-HG and alter DNA methylation, our experiments do not prove a causal role for these downstream changes and disease etiology or maintenance.…”
Section: A Mouse Aml Model Driven By Idh2 Mutants Suggests Therapeuticontrasting
confidence: 37%
“…IDH2 mutant proteins promote AML by blocking the differentiation of HSPCs; in the absence of a cooperating event, this produces an MDS-like state, a disorder in which IDH2 mutations are frequent in humans (Patnaik et al 2012). While these effects correlate with the ability of IDH2 mutants to produce 2-HG and alter DNA methylation, our experiments do not prove a causal role for these downstream changes and disease etiology or maintenance.…”
Section: A Mouse Aml Model Driven By Idh2 Mutants Suggests Therapeuticontrasting
confidence: 37%
“…TET2 mutation is more common in MDS/MPN than in AML, whereas IDH1/2 mutations are more frequent in AML than MDS/MPN [1,2]. When present in MDS, IDH1 mutation is associated with shorter leukemia-free survival and decreased overall survival, whereas these impacts are not found in TET2-mutated MDS [38,39]. Furthermore, Fig.…”
Section: Tet2 and Idh1/2 Mutations In Hematological Disordersmentioning
confidence: 85%
“…Interestingly, it has been demonstrated that TET2 function is also compromised by 2-hydroxyglutarate, an oncogenic metabolite produced by gain-of-function mutations of isocitrate dehydrogenase (IDH) 1 and 2, which has been shown to occur mutually exclusive with regard to TET2 mutations in 3.5-12% of MDS patients. 5,8,[11][12][13][14][15][16] Until now, several studies carried out have addressed the clinical relevance of TET2 and IDH1/2 mutations in MDS. 4,6,8,[11][12][13] The prevalent view is that there is no significant impact of TET2 mutations on overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%